Pharmacokinetics of mycophenolic acid in plasma and peripheral blood mononuclear cells and its relationship with activity of inosine monophosphate dehydrogenase in Chinese adult kidney allograft recipients - Lu, Yun-Zhu; Lu, Xiao-Ling; Lu, Jia-Qian; Shao, Kun; An, Hui-Min; Zhou, Pei-Jun; Shi, Hao-Qiang; Chen, Bing (Frontiers in Pharmacology, 2025)
AimsWe aimed to study the pharmacokinetics (PK) of mycophenolic acid (MPA) in plasma and peripheral blood mononuclear cells (PBMCs) and the relationship of MPA in plasma and PBMC with activity of inosine monophosphate dehydrogenase (IMPDH) in Chinese kidney allograft recipients.MethodsPlasma and PBMC samples were collected 0–12 h after administration of mycophenolate mofetil (MMF) or enteric-coated mycophenolate sodium (EC-MPS) 2 weeks after initiation of immunosuppressive therapy. MPA concentrations in plasma and PBMCs and IMPDH activity were determined using liquid chromatography–mass spectrometry. The PK and pharmacodynamic parameters was estimated. The relationship between plasma and PBMC MPA levels and IMPDH activity was determined using the inhibitory Emax model.ResultsTotally 24 patients receiving MMF and 19 patients receiving EC-MPS were included in the study. A significant positive correlation was observed between the C0 (r = 0.535, P = 0.007), Cmax (r = 0.538, P = 0.007), and AUC0–12h (r = 0.472, P = 0.02) of plasma and PBMC MPA in patients who received MMF. IMPDH activity exhibited a negative correlation with MPA plasma and PBMC concentrations. Significant relationship was observed between MPA exposure and IMPDH activity in PBMC (r = 0.398, P = 0.01). The IC50 of plasma and PBMC MPA on IMPDH activity were 2.76 μg/mL and 0.023 ng/106 cells for MMF, 3.34 μg/mL and 0.052 ng/106 cells for EC-MPS, respectively.ConclusionMeasurement of MPA concentration and IMPDH activity in PBMCs serves as a complementary method to routine clinical therapeutic drug monitoring, which provide basis for the individual therapy of MPA in Chinese kidney allograft recipients.